ASPEK KEBUDAYAAN DALAM PUISI “SELENDANG BATIK IBU” KARYA AMALIA NAJICHAH - Pebriyanti, Firda; Teska, Sanda Amelia; Listiyani, Serly; Julianto, Indra Rasyid (PT. CASA CENDEKIA MEDIA, 2025)
The purpose of this research is to describe the aspects of cultural values, and symbols contained in the poem